2011
DOI: 10.1038/bjc.2011.230
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour markers can define patients with normal colons, benign polyps, and cancers

Abstract: Background:Early diagnosis represents the best opportunity for cure of colorectal cancer. Current screening programmes use faecal occult blood testing for screening, which has limited sensitivity and poor specificity.Methods:In this study we looked at a series of previously described diagnostic markers utilising circulating free DNA (cfDNA), with a preparation method allowing small DNA fragments to be isolated. The Circulating free DNA was isolated from samples obtained from 85 patients, including 35 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 65 publications
7
71
3
Order By: Relevance
“…In general, the levels are higher in mCRC patients than in healthy controls, as shown in Table 1 [15,20,47,58,[63][64][65][66][67][68][69][70][71][72]; and the levels have some correlation to stage as reported in a limited number of studies [15,41,68,73] in primary CRC. These findings give important biological information, and researchers suggest that cfDNA has potential as a diagnostic or screening tool; a potential that is currently being investigated by several groups.…”
Section: Methodsmentioning
confidence: 71%
“…In general, the levels are higher in mCRC patients than in healthy controls, as shown in Table 1 [15,20,47,58,[63][64][65][66][67][68][69][70][71][72]; and the levels have some correlation to stage as reported in a limited number of studies [15,41,68,73] in primary CRC. These findings give important biological information, and researchers suggest that cfDNA has potential as a diagnostic or screening tool; a potential that is currently being investigated by several groups.…”
Section: Methodsmentioning
confidence: 71%
“…In addition, their multiplexing power is restricted, limiting the simultaneous analysis of additional emerging biomarkers. These limitations may be overcome by next generation sequencing (NGS), which enables the sequencing of large genomic regions or several exons on ctDNA (7)(8)(9). However, the requirement in this setting of a high degree of sensitivity may easily lead to false positive results, which underlines the need of a careful validation of a number of critical points, including blood collection, cfDNA extraction, library preparation, sequencing and variant calling (Figure 1).…”
Section: Review Articlementioning
confidence: 99%
“…In most clinical trials, EDTA containing tubes (Vacutainer) were used for blood collection (4)(5)(6)(7)(8)(9). This approach avoids clotting and allows obtaining the plasma sample, Is particularly important, after the blood collection, to proceed with plasma preparation by centrifugation within 1 h, as ctDNA is associated with a high turn-over (15 min half-life).…”
Section: Blood Collection and Cfdna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The understanding of colorectal cancer (CRC) biology is rapidly growing and several molecular pathways including Wnt-β-catenin, TGF-β and epidermal growth factor receptor (EGFR) signalling have been identified that are deregulated at different stages of colon carcinogenesis [2,3]. Genetic alterations in CRC show promise as potential biomarkers for early cancer diagnosis as well as in selection of patients for treatment [4][5][6][7][8]. In recent years targeted therapies inhibiting EGFR signalling have been introduced into clinical practice resulting in improvement of overall survival of a subset of patients with advanced metastatic disease.…”
Section: Introductionmentioning
confidence: 99%